Winery wastewater treatment: a critical overview of advanced biological processes. (19th May 2019) - Bolzonella, David; Papa, Matteo; Da Ros, Cinzia; Anga Muthukumar, Lokeshwer; Rosso, Diego
Abstract: Wine production is one of the leading sectors of the food processing industry. The wine industry produces a large amount of wastewater characterized by a high strength in terms of organic pollution and large variability throughout the year. Most of the organic matter is soluble and easily biodegradable. On the other hand, nitrogen and phosphorous are lacking. The aerobic and anaerobic processes are largely applied for winery wastewater treatment because they can quickly react to changes in the organic loading. This review analyzes e applied biological systems, considering both aerobic and anaerobic processes, and different reactor configurations. The performances of different biological processes are evaluated in terms of operational conditions (organic loading rate and hydraulic retention time). Aerobic processes can guarantee chemical oxygen demand removal up to 98% for organic loading rates of some 1-2 kg of chemical oxygen demand m −3 d −1 but requires good aeration systems to supply the required process oxygen. The management cost of these processes could be high considering the power density in the range 60-70 W m −3 reactor and that nutrients should be added to support biomass growth. On the other hand, anaerobic processes are able to face high organic loads with low running costs, but COD removal is generally limited to 90%. Combination of the two treatment systems (anaerobic followed by aerobic) could reduce management costs and meet high discharge standards.